A skywatcher's year - Kanipe, Jeff, 1953- (Cambridge University Press, 1999)
Through 52 essays, A Skywatcher's Year guides readers to celestial events and phenomena that occur or are visible with the naked eye and binoculars for each week of the year. It acquaints readers not only with up-to-date astronomical information on stars, nebulae, meteors, the Milky Way, and galaxies, but also conveys the beauty and wonder of the night sky. Covering both the Northern Hemisphere and the Southern Hemisphere, A Skywatcher's Year helps readers find prominent stars and constellations, bright star clusters, nebulae, and galaxies, and explains how and when to observe prominent annual meteor showers.